Веселая семейка: [для среднего школьного возраста] / иллюстрации Марины Мордвинцевой - Носов Николай Николаевич (Эксмо, 2021)
Экземпляры: (20231002) / Инвентарный номер: 65210 / Цена: 555.00 / Сис.шифр: Р2ср / Авт.знак: Н 84 / ГРНТИ: 17.82.82 / ББК: 84(2Рос=Рус)6